Capital Intensity, Leverage, Return on Asset, dan Ukuran Perusahaan Terhadap Agresivitas Pajak - Andi Prasetyo; Sartika Wulandari (Jurnal Akuntansi, 2021)
Tax aggressiveness is the act of manipulating profits carried out through tax planning that can be both legal and illegal. Measurement of tax aggressiveness using the comparison formula for tax expense and income (ETR). The purpose of this study is to test whether there is an effect of Capital Intensity, Leverage, Return on Assets, and Company Size on Tax Aggressiveness. This type of research includes quantitative research using secondary data obtained from company financial reports. The population of this study is all manufacturing companies listed on the Indonesia Stock Exchange in the 2017-2019. The sampling technique used purposive sampling with the criteria of manufacturing companies listed on IDX, the financial reports in rupiah, and manufacturing companies with an ETR value of less than one. The samplehas met the criteria of 249 companies. The data analysis method used is panel data regression using Eviews 9.0. The results showed that Capital Intensity, Leverage,ROA and Firm Size have no effect on Tax Aggressiveness. The result of this study have implications for the Directorate General of Taxes (DGT) to detect the practice of tax aggressiveness by companies. Keywords: Tax Agressiveness, Capital Intensity, Leverage, ROA,and Firm Size